Long-term patient-reported outcome measures after injury: National Trauma Research Action Plan (NTRAP) scoping review protocol. Issue 1 (28th May 2020) - Herrera-Escobar, Juan Pablo; Castillo-Angeles, Manuel A; Osman, Samia Y; Orlas, Claudia P; Janjua, Mahin B; Abdullah-Arain, Muhammad; Reidy, Emma; Jarman, Molly P; Price, Michelle A; Bulger, Eileen M; Nehra, Deepika; Haider, Adil H
Abstract : Background: A significant proportion of patients who survive traumatic injury continue to suffer impaired functional status and increased mortality long after discharge. However, despite the need to improve long-term outcomes, trauma registries in the USA do not collect data on outcomes or care processes after discharge. One of the main barriers is the lack of consensus regarding the optimal outcome metrics. Objectives: To describe the methodology of a scoping review evaluating current evidence on the available measures for tracking functional and patient-reported outcomes after injury. The aim of the review was to identify and summarize measures that are being used to track long-term functional recovery and patient-reported outcomes among adults after injury. Methods: A systematic search of PubMed and Embase will be performed using the search terms for the population (adult trauma patients), type of outcomes (long-term physical, mental, cognitive, and quality of life), and measures available to track them. Studies identified will be reviewed and assessed for relevance by at least two reviewers. Data will be extracted and summarized using descriptive statistics and a narrative synthesis of the results. This protocol is being reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines. Dissemination: This scoping review will provide information regarding the currently available metrics for tracking functional and patient-reported outcomes after injury. The review will be presented to a multi-disciplinary stakeholder group that will evaluate these outcome metrics using an online Delphi approach to achieve consensus as part of the development of the National Trauma Research Action Plan (NTRAP). The results of this review will be presented at relevant national surgical conferences and published in peer-reviewed scientific journals.